Output Current Ripple and Efficiency Optimal Control Method for Multi-Phase Interleaved LLC Resonant Converter - Wang, Weikang; Liu, Yang; Zhao, Jin; Yin, Quan; Lv, Qiaoqiang; Zhang, Peng (Frontiers in Energy Research, 2022)
The interleaving technique is required for LLC resonant converters to achieve high power levels, handle higher input/output currents, and reduce output current ripple. However, the high system efficiency and the low output current ripple for the multi-phase LLC resonant converter cannot be achieve at the same time at low and medium power levels. Most methods try to keep the multi-phase LLC resonant converter in load-sharing mode regardless of the power level, which will result in low system efficiency at low and medium power levels. In this paper, an output current ripple and efficiency optimal control method with finite load distribution schemes is proposed for the multi-phase LLC resonant converter to balance the efficiency and output current ripple. The optimal control method improves the efficiency as much as possible while keeping output current ripple low. According to the calculation of output current ripple and efficiency, the optimal load distribution scheme is selected. The pulse-frequency modulation (PFM) and phase-shift modulation (PSM) hybrid control is applied to regulate the load of each phase. An analysis is provided, and a 540-W three-phase interleaved LLC resonant converter is built to verify the superiority.